2008
DOI: 10.1111/j.1462-2920.2008.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Active bacterial community structure along vertical redox gradients in Baltic Sea sediment

Abstract: SummaryCommunity structures of active bacterial populations were investigated along a vertical redox profile in coastal Baltic Sea sediments by terminal-restriction fragment length polymorphism (T-RFLP) and clone library analysis. According to correspondence analysis of T-RFLP results and sequencing of cloned 16S rRNA genes, the microbial community structures at three redox depths (179 mV, -64 mV and -337 mV) differed significantly. The bacterial communities in the community DNA differed from those in bromodeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
56
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 44 publications
7
56
2
3
Order By: Relevance
“…Under anoxic conditions, many cyanobacteria are able to gain energy from fermentation of storage carbohydrates accumulated during photoautotrophic growth, but fermentation of external organic substrates in free-living cyanobacteria is poorly documented (14). Viability and growth of cyanobacteria under dark anoxic conditions have also been observed in Baltic Sea sediment, based on 16S rRNA libraries and incorporation of bromodeoxyuridine into DNA (15). Recently, Kamp et al (16) reported that diatoms are able to perform dissimilatory nitrate reduction of intracellular stored nitrate under anoxic dark conditions, which may aid in their survival in anoxic sediments.…”
mentioning
confidence: 89%
“…Under anoxic conditions, many cyanobacteria are able to gain energy from fermentation of storage carbohydrates accumulated during photoautotrophic growth, but fermentation of external organic substrates in free-living cyanobacteria is poorly documented (14). Viability and growth of cyanobacteria under dark anoxic conditions have also been observed in Baltic Sea sediment, based on 16S rRNA libraries and incorporation of bromodeoxyuridine into DNA (15). Recently, Kamp et al (16) reported that diatoms are able to perform dissimilatory nitrate reduction of intracellular stored nitrate under anoxic dark conditions, which may aid in their survival in anoxic sediments.…”
mentioning
confidence: 89%
“…The steep halocline in the Baltic Proper, together with considerable eutrophication, leads to extreme differences in environment, such that very different microbial processes may dominate above and below the halocline. A number of studies have provided insights on the taxonomic diversity of microbial communities both in the water column [9], [10], [11], [12], [13] and coastal sediment [14], [15] while the study of functional capacity has primarily focused on specific functions [16], [17], [18], [19], [20], [21], [22], [23], [24] and the study of total community function in the Baltic Proper is therefore still in its infancy.…”
Section: Introductionmentioning
confidence: 99%
“…To determine microbial diversity between samples, terminal restriction fragment length polymorphism (t-RFLP) analysis of bacterial and archaeal rRNA genes was performed on samples from both India and NCM. Each DNA suspension was amplified using the general bacterial primers 27F-FAM and 926R (11) or general archaeal primers 21F-FAM and 958R (6) in a MasterCycler thermocycler (Eppendorf, Westbury, NY). Each 20-l PCR mixture contained 1.25 units of AmpliTaq Gold LD (ABI, Foster City, CA), 1ϫ PCR buffer, 4 mM MgCl 2 , 800 M each deoxynucleoside triphosphate, 0.5 M each primer, and 8 g of bovine serum albumin.…”
mentioning
confidence: 99%